The Risk of COVID-19 in People Having a Particular Set of Gene - Dhakal, B.; Makaju, R.; Dhakal, R. (Kathmandu University Medical Journal, 2021)
These risk factors of advancing age, male gender and co-existing health conditions like cancer, cardiovascular diseases, diabetes and obesity do not fully explain why some people have no or mild symptoms whereas others have severe symptoms. Genomewide association study (GWAS) identify a 3p21.31 gene cluster as a genetic susceptibility locus in patients with COVID-19 with respiratory failure. They also found a higher risk among persons with blood group A and protective effect for blood group O than among patients with other blood groups. The particular haplotype in a region of chromosome 3 is contributed to modern humans by neandertals. Another Neanderthal haplotype on chromosome 12 is associated with a 22% reduction in relative risk of becoming severely ill with COVID-19. The ApoE e4e4 homozygous genotype was found to increase the risk of severe COVID-19. Change in angiotensin converting enzyme (ACE) 2 gene was also found to be associated with increased risk of COVID-19, cardiovascular and pulmonary conditions.